Augmentative and alternative communication from the perspective of professionals working in palliative care in the hospital context (Research, Society and Development, 2022)
This study aimed to verify the use of alternative and expanded communication by professionals working in palliative care in the hospital context with the adult and elderly population. This is a study pilot involving a field survey with a quantitative-qualitative approach. Data collection took place through an online questionnaire, with data analyzed using simple descriptive statistics and content analysis. Fifteen health professionals participated in this research, who consensually expressed the level of maximum importance attributed to the communication skill in palliative care, a factor supported by three central ideas: basis of palliative practice, path to singular therapeutic planning and active participation of the patient. patient in treatment and a tool for multidimensional assessment of suffering. However, in the face of clinical conditions in which the patient's communication is altered, some professionals mentioned a lack of preparation to provide communication through alternative resources. When using resources for expanded alternative communication, it was noticed that the approach is limited, focused especially on the identification of symptoms and basic needs. It was found that there is clarity among the participants about the importance of communication in the care process and that the deprivation of spaces for expression and exchanges constitutes a potential element of suffering. In view of this understanding, part of the professionals mentioned strategies used within poorly systematized actions, a factor associated with low instruction on assistive resources and the absence of a multiprofessional hospital team to support such implementations.